The Urgency of Character Education for Islamic Religious Education Teachers - Indah Fujianti (EDUJAVARE: International Journal of Educational Research, 2026)
Character education has become a central concern in global educational discourse due to increasing moral degradation, social fragmentation, and ethical crises among younger generations. This study aims to analyze the urgency of character education for Islamic Religious Education teachers in shaping students’ moral and ethical development in the modern era. The research employs a Systematic Literature Review (SLR) method to systematically identify, evaluate, and synthesize relevant scholarly literature from various academic databases such as Scopus, ERIC, and Google Scholar. The selected studies were analyzed using inclusion and exclusion criteria focusing on publications related to character education, Islamic education, and teacher roles. The findings indicate that character education in Islamic Religious Education is fundamentally grounded in the integration of faith, knowledge, and moral values, where teachers play a central role as moral models in students’ character formation. However, its implementation faces significant challenges, including digital disruption, limited instructional time, curriculum constraints, and inadequate teacher preparedness. Despite these challenges, effective strategies such as value integration across curricula, contextual learning approaches, and collaboration between schools, families, and communities can enhance the effectiveness of character education. The study concludes that strengthening Islamic Religious Education teachers’ competence and commitment is essential to ensuring sustainable character development in students within contemporary educational contexts